Implementation of External Quality Assurance System in North Sulawesi - E. Wawo, Merry; A.M. Rawis, Joulanda; A. Katuuk, Deitje; S. J. Lengkong, Jeffry (CV. Inara, 2021)
The role of external institutions in education quality assurance is very important in the External Quality Assurance System (SPME). This research is about the Implementation of Education Quality Assurance in North Sulawesi especially at Bitung City and Tomohon City. This research was conducted on planning the quality of education, quality of education, and evaluation of the quality of education in the Department of Education and Culture of Bitung City and Tomohon City. The research problems are: 1) How is the quality of education planning in Bitung City and Tomohon City?; and2) How is the implementation of the quality of education in Bitung City and Tomohon City?.This study used a qualitative approach with descriptive methods designed for a multi-site study design. Data were collected through observation, interviews and documentation. The data analysis used includes simultaneous process flow of activities, namely data reduction, data presentation, and conclusions.The results of this study indicate that: 1) Education quality planning in Bitung City and Tomohon city is carried out through joint meetings to focus more on program activities and strengthen appropriate and targeted activity programs. Planning for quality fulfillment in Bitung City is the result of recommendations for improvement from quality mapping activities, namely quality data analysis, namely standards, recommendations for improvement, volume, funding requirements. Quality planning in Tomohon City is carried out by implementing the implementation steps of the preparation of a quality fulfillment plan within the Tomohon City Education and Culture Office carried out by forming a regional education quality assurance team (TPMPD).2) Implementation of Education Quality Fulfillment in Bitung City is focused on process standards, facilities and infrastructure standards and educator standards. This is adjusted to the conditions during the COVID-19 pandemic. Teacher Competency Improvement Program, namely activities carried out in the form of Distance Learning (PJJ) socialization, RPP Simplification Workshop, and Basic Competency Analysis. The implementation of quality fulfillment is carried out online and face-to-face for certain areas that are difficult to connect to the internet by paying attention to health protocols.